Devising a method to control the operational quality and reliability of fiber-optical communication lines - Kiforuk, Sergii (Eastern-European Journal of Enterprise Technologies, 2021)
The lack of recommendations in the normative and technical documentation related to fiber-optic communication lines (FOCL) for assessing their technical condition necessitated devising a method to control the lines' quality and reliability of operation. The method creates the basis for calculating the quality and reliability indicators of FOCL operation and suggests measures to improve them. It determines the methods of control, as well as the acquisition, accounting, and analysis of damage statistics with and without interruption of communication. The graphic sequence of implementation of the stages of the method demonstrates that resolving the task to control these indicators should involve: – managing the acquisition and actual acquisition of operational data on damages (the causes, nature, quantity, the duration of communication breakdown and complete elimination of damage); – determining the quality and reliability indicators of FOCL operation annually; – analysis of the obtained results and the development (correction) of measures to comply with the norms of these indicators; – the implementation of measures to comply with the norms of quality and reliability of FOCL operation (if necessary). Based on the operational data from a line operator acquired over three years in the specified climatic zone (a cable of the type OKLBg-3 DA12-3×4E-0.4F3.5/0.22N18-12/0), the methodical component of the method was examined. The obtained results on the operational quality (damage density, average damage duration, break (downtime) of communication) and reliability indicators (FOCL readiness factor) of a subscriber access network without reservation showed that the line had low efficiency. The communication breakdown over three years amounted to K=12,569.8 stream∙hours. The downtime at this volume of digital stream∙hours has led to significant economic losses. Line operators have been given recommendations for the proper FOCL operation and ensuring a normalized value of the line readiness coefficient. To this end, it is necessary to reduce the time to re-link and prolong the line's failure-free operation